2006
DOI: 10.1149/1.2196672
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface pH on Electrodeposited Ni Films

Abstract: Ni metal was potentiostatically electrodeposited on a vertical plane cathode in a Watts bath in order to determine the effect of the cathode surface pH on the Ni film microstructure. Polarization curves and current efficiencies were measured at pH values of 1.5, 3.4, and 5.5. The surface pH value ͑pH s ͒ was estimated from the measured partial current density for hydrogen gas evolution based on a steady-state one-dimensional mass transfer model. Any species relating to the buffering function through the dissoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 43 publications
0
45
0
Order By: Relevance
“…This may lead to the formation of different dendrites. Very recent studies showed that electrochemical conditions such as surface pH and overpotential affect the structure of electrodeposited metal films [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…This may lead to the formation of different dendrites. Very recent studies showed that electrochemical conditions such as surface pH and overpotential affect the structure of electrodeposited metal films [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Ni electrodeposition is usually performed at high temperatures (50-70°C) and at high current densities. [17][18][19][20] Electrodeposition of Ni has been reported both through direct current [21][22][23][24][25] and pulse 26 methods. The literature reveals that in direct current electrodeposition, an increase in current density leads to a corresponding decrease of the grain size of the deposits, this behavior being attributed to the evolution of more hydrogen at the cathode interface at higher current densities.…”
Section: Introductionmentioning
confidence: 99%
“…The change of grain size may be explained by the hydrogen evolution, which is favoured at low pH. Recent studies [5,6] showed that deposition parameters, for example pH, affect the microstructure of electrodeposited metal films.…”
Section: Resultsmentioning
confidence: 99%